Chemical profiling and biological activity of Peperomia blanda (Jacq.) Kunth - Al-Madhagi, Wafa M.; Hashim, Najihah Mohd; Ali, Nasser A. Awad; Alhadi, Abeer A.; Halim, Siti Nadiah Abdul; Othman, Rozana (PeerJ, 2018)
Background. Peperomia belongs to the family of Piperaceae. It has different uses in folk medicine and contains rare compounds that have led to increased interest in this genus. Peperomia blanda (Jacq.) Kunth is used as an injury disinfectant by Yemeni people. In addition, the majority of Yemen's population still depend on the traditional remedy for serious diseases such as cancer, inflammation and infection. Currently, there is a deficiency of scientific evidence with regards to the medicinal plants from Yemen. Therefore, this study was performed to assess the chemical profile and in vitro antioxidant and cytotoxic activities of P. blanda. Methods. Chemical profiling of P. blanda was carried out using gas chromatography mass spectrometry (GCMS) followed by isolation of bioactive compounds by column chromatography. DPPH• and FRAP assays were used to evaluate antioxidant activity and the MTT assay was performed to estimate the cytotoxicity activity against three cancer cell lines, namely MCF-7, HL-60 and WEHI-3, and three normal cell lines, MCF10A, WRL-68 and HDFa. Results. X-ray crystallographic data for peperomin A is reported for the first time here and N, N0-diphenethyloxamide was isolated for the first time from Peperomia blanda. Methanol and dichloromethane extracts showed high radical scavenging activity with an IC50 of 36.81 ± 0.09 μg/mL, followed by the dichloromethane extract at 61.78 ± 0.02 μg/mL, whereas the weak ferric reducing activity of P. blanda extracts ranging from 162.2 ± 0.80 to 381.5 ± 1.31 μg/mL were recorded. In addition, petroleum ether crude extract exhibited the highest cytotoxic activity against all the tested cancer cell lines with IC50 values of 9.54 ± 0.30, 4.30 ± 0.90 and 5.39 ± 0.34 μg/mL, respectively. Peperomin A and the isolated mixture of phytosterol (stigmasterol and β-sitosterol) exhibited cytotoxic activity against MCF-7 and WE-HI cell lines with an IC50 of (5.58 ± 0.47, 4.62 ± 0.03 μg/mL) and (8.94 ± 0.05, 9.84 ± 0.61 μg/mL), respectively, compared to a standard drug, taxol, that has IC50 values of 3.56 ± 0.34 and 1.90 ± 0.9 μg/mL, respectively. Conclusion. The activities of P. blanda extracts and isolated compounds recorded in this study underlines the potential that makes this plant a valuable source for further study on anticancer and antioxidant activities.